THE SOCIAL-ECONOMIC CONDITION OF THE POPULATION RELOCATED TO THE LAND TO BE DEVELOPED AT THE INITIAL TIME - J.B. Jumayev (American Journals Publishing, 2024)
This article talks about the initial socio-economic situation of the population relocated to the reserves and gray lands being developed in our republic, as well as the problems that arose in providing them with housing.
Keywords: Protection campaign, field, Uzbek SSR, Samarkand region, Nurota oasis, General Resettlement Department, Resettlement Department, collective farm, state farm, social assistance.